2011
DOI: 10.1177/1043454211409587
|View full text |Cite
|
Sign up to set email alerts
|

Parental Experiences of Information Within Pediatric Oncology

Abstract: 901 87 Umeå, Sweden. +46 (0)90-786 91 54, anders.ringner@nurs.umu.se. Ringnér et al., Parental experiences of information within pediatric oncology 2 AbstractParents of children with cancer use information to create knowledge about their child's disease. Information can help parents reduce chaos and create a feeling of control, but there are often obstacles to its acquisition, which has been described as similar to learning a new language. The purpose of this study was to describe parents' experiences of acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
79
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 25 publications
4
79
1
Order By: Relevance
“…The role of communication is important in the pediatric cancer setting where patients and families need to understand complex information in order to make critical medical decisions. Empathetic communication is particularly important at the time of a child's diagnosis of cancer, when parents experience significant levels of stress and anxiety that affect their understanding of the medical information provided . Unlike other points in the cancer experience where parents make major decisions about their child's cancer therapy (relapse, end‐of‐life), the diagnostic consultation has a more complex agenda.…”
Section: Introductionmentioning
confidence: 99%
“…The role of communication is important in the pediatric cancer setting where patients and families need to understand complex information in order to make critical medical decisions. Empathetic communication is particularly important at the time of a child's diagnosis of cancer, when parents experience significant levels of stress and anxiety that affect their understanding of the medical information provided . Unlike other points in the cancer experience where parents make major decisions about their child's cancer therapy (relapse, end‐of‐life), the diagnostic consultation has a more complex agenda.…”
Section: Introductionmentioning
confidence: 99%
“…Parents of children and adolescents with cancer have indicated that information about the cancer was critical in helping them to cope emotionally with the situation (Ringnér et al, 2011a) and to reduce chaos and create a feeling of control (Ringnér et al, 2011b). Therefore, when designing a brief therapeutic conversation intervention for families of children in active cancer treatment, the relationship between how the information is delivered and in what way parents are offered the emotional and psychosocial support is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…It is of great importance to keep parents sufficiently informed, especially because, within paediatric oncology, parents are not currently entirely satisfied with the amount and timing of information [20, 21]. Furthermore, lack of information to parents in paediatric cancer care leads to a feeling of being unwelcome and abandoned [22]. Parents and patients often receive an insufficient level and amount of information, leading to conflict in care [23].…”
Section: Discussionmentioning
confidence: 99%